ISSUES OF RENDERING MILITARY TERMINOLOGY WITHIN THE FRAMEWORK OF MILITARY DISCOURSE - Seidikenova A. С.; Akkari, A. A.; Bakitov, A.; Morugova, Y. (Farabi Journal of Social Sciences, 2020)
This article takes an attempt to review the complexity of rendering military terminology in two languages and its subsequent identification of structure-forming features. The processes of globalization are incredibly intense, the military services of the world powers have to communicate with each other using military terminology in the course of hostilities and in the framework of military cooperation (competitions of military personnel, all kinds of military forums). The armed forces and the army are one of the most important social institutions and apparatuses in many countries. In the zones of local military conflicts, with the assistance of the armed forces, missions and humanitarian convoys are carried out aimed at establishing and maintaining a ceasefire and normal life. That is why, this research focuses on the study of military discourse and its functional components taking into account the increasing demand for developing multilingual vocabulary and speech strategies owing to current international conflicts.